PENGARUH HARGA, KUALITAS PRODUK, KUALITAS LAYANAN, TERHADAP KEPUASAN PELANGGAN PADA RUMAH MAKAN BEBEK DAN AYAM GORENG PAK NDUT DI SAMARINDA - Yuni Diah Saraswati (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
The problem occurred in Rumah Makan Bebek Pak Ndut based on observations conducted by researchers after conducting interviews to customers showed that customers still feel less satisfied with the price, quality of products and services. The price applied is still at a value less precise by some customers, the quality of the product is less in accordance with the expected and the service that looks less to customers who ask for orders that do not come. This research aims to determine the significance of the effect of price (X1), product quality (X2) and quality of service (X3) partially and simultaneously to customer satisfaction (Y) as well as to know and analyze the most influential customer satisfaction in the Pak Ndut restaurant in Samarinda ". Primary Data is obtained by spreading the questionnaire to the customers. Secondary Data is obtained by conducting field observations. Data was analyzed using simple linear regression techniques with the help of SPSS statistical version 22. The results of this study were price variables and service quality variables partially influential insignificant to the customer satisfaction variables while the product quality variables partially impact significantly on the customer satisfaction variables, price variables, product quality and service quality simultaneously influence insignificant to the customer satisfaction variables and the most significant product quality variables against customer satisfaction variables. Rumah Makan Bebek Dan Ayam Goreng Pak Ndut The price that is set by the restaurant should be adjusted again with the quality of the customer received, in terms of quality products can be done by providing training to employees in the field of condiments so that the taste is maintained and does not eliminate the characteristic and improve the quality of service.